Distribution and importance of spiders inhabiting a Brazilian sugar cane plantation - Rinaldi, Isabela Maria Piovesan [UNESP]; Mendes, Beatriz do Prado [UNESP]; Cady, Alan Bruce (Sociedade Brasileira de Zoologia, 2002)
The spider fauna (Araneae) of a sugar eane plantation was surveyed monthly by hand colteetion and beating vegetation in sugar cane fields across Botucatu, State of São Paulo, Brazil. Composition and rchness (family and species where identifieation to species was possible) microhabitat preferenees were reeorded, and diversity and evenness indices were calculated. A total of 1291 spiders belonging to 73 species and 20 families were collected. The most diverse families were Theridiidae, Salticidae, and Araneidae, and the most abundant ones were Theridiidae, Saltieidae, Anyphaenidae, and Araneidae, Seven species represented 58.6% of the total fauna, with Crysso pulcherrima (Mello-Leitão,1917) (Theridiidae) composing 28.2%. About 65% of the spiders occupied the upper part of the plants (above 20 cm). Five spider species were present in the sugar cane throughout crop development. Evidence of spiders feeding on sugar cane pest species was observed.
Keywords: Araneae; Sugar cane plantation; spider fauna; spider diversity; natural enemies